2019
DOI: 10.7150/thno.36077
|View full text |Cite
|
Sign up to set email alerts
|

The role of Nav1.7 and methylglyoxal-mediated activation of TRPA1 in itch and hypoalgesia in a murine model of type 1 diabetes

Abstract: Methylglyoxal (MGO), an endogenous reactive carbonyl compound, plays a key role in the pathogenesis of diabetic neuropathy. The aim of this study is to investigate the role of MGO in diabetic itch and hypoalgesia, two common symptoms associated with diabetic neuropathy. Methods : Scratching behavior, mechanical itch (alloknesis), and thermal hypoalgesia were quantified after intradermal (i.d.) injection of MGO in naïve mice or in diabetic mice induced by intraperitoneal (i.p.) injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 75 publications
3
33
0
Order By: Relevance
“…This model resembles the key features of T1DM patients with a loss of β-cell function and the development of hyperglycemia 46 - 48 . At present, the STZ-induced mouse model is one of the most widely used animal models of human autoimmune diabetes in T1DM studies 46 , 49 - 51 . In our study, we focused the effect of circPPM1F on development of STZ-induced diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…This model resembles the key features of T1DM patients with a loss of β-cell function and the development of hyperglycemia 46 - 48 . At present, the STZ-induced mouse model is one of the most widely used animal models of human autoimmune diabetes in T1DM studies 46 , 49 - 51 . In our study, we focused the effect of circPPM1F on development of STZ-induced diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Itch-related ion channels are the key regulators in itch progression [20]. Recent evidence has indicated that the TTX-S VGSC subtype Nav1.7 in primary sensory neurons plays a significant role in mediating itching [15,17,18]. The discovery of novel gating modifiers of Nav1.7 should hold significant potential for effective treatment of itching.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a monoclonal antibody that suppresses Nav1.7 activity by interacting with the voltage sensor effectively inhibits the histamine-dependent itch in mice [17]. Recently, it was reported that the pharmacological blockade of Nav1.7 reduced itching induced by methylglyoxal or in streptozotocin-induced diabetic mice, indicating that Nav1.7 played a key role in itching in a mouse model of type 1 diabetes [18]. All of these significant findings suggest that Nav1.7 is a novel and promising target for itch management.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Ca v 3.2 inhibitor failed to inhibit touch-evoked scratching in a mouse model of type Ι diabetes. [59] Further research should be undertaken to investigate whether hydrogen sulphide, Cav3.2, Aδ-LTMRs and C-LTMRs contribute to mechanical itch sensitization under chronic itch conditions.…”
Section: Hypersensitivity Of Itch Pathway Neuronsmentioning
confidence: 99%